Pengaruh Brand Image Dan Kepuasan Terhadap Purchase Intention Pada Tiktok Shop (Studi Pada Generasi Zilenial) - Gusti Ayu Aghivirwiati (Institut Teknologi dan Sains Mandala, 2024)
The millennial generation currently has the convenience of accessing various kinds of applications, one of which is TikTok. TikTok provides online or online shopping features that allow anyone to make money through the features provided, namely the TikTok Shop, an online shopping feature offered by the TikTok platform. The purpose of this study is to find out and explain the influence of brand image and satisfaction on purchase intention at Tiktok Shop, and to know and explain the role of satisfaction in mediating the influence of brand image on purchase intention at Tiktok Shop. This research was conducted on tiktok users in Indonesia. The number of samples used in this study were 160 people. The analysis technique used is SEM-PLS. The results of this study indicate that brand image and satisfaction affect purchase intention, and satisfaction is able to mediate the effect of brand image on purchase intention.